NIH4215: A mutation-prone thiamine auxotrophic clinical Aspergillus fumigatus isolate - Peres da Silva, Roberta; Brock, Matthias (Frontiers in Fungal Biology, 2022)
Aspergillus fumigatus is the main cause of life-threatening invasive aspergillosis. Despite the availability of various antifungals, therapy remains challenging and requires further studies. Accordingly, the clinical A. fumigatus isolate NIH4215 deriving from a fatal case of human pulmonary aspergillosis has frequently been used in drug efficacy studies. Unexpectedly, our initial attempts to generate a bioluminescent reporter of strain NIH4215 for in vivo drug efficacy studies failed, as NIH4215 was unable to grow on defined minimal medium. Subsequent analyses discovered a previously undescribed thiamine auxotrophy of strain NIH4215 and transformation with thiamine biosynthesis genes from A. fumigatus strain Af293 identified the nmt1 gene as cause of the thiamine auxotrophy. Sequencing of the defective nmt1 gene revealed the loss of a cysteine codon within an essential iron-binding motif. Subsequently, the wild-type nmt1 gene was successfully used to generate a bioluminescent reporter strain in NIH4215 by simultaneously deleting the akuB locus. The resulting bioluminescent ΔakuB strains showed a high frequency of homologous integration as confirmed by generation of pyrG and niaD deletion mutants. When tested in a Galleria mellonella infection model, neither thiamine auxotrophy nor the deletion of the akuB locus had a significant effect on virulence. However, besides thiamine auxotrophy, sectors with altered morphology and albino mutants frequently arose on colony edges of strain NIH4215 and its derivatives, and stable albino mutants were successfully isolated. A proposed increased mutation rate of NIH4215 was confirmed by screening for spontaneous occurrence of fluoorotic acid resistant mutants. Independent mutations in the pyrG and pyrE gene were identified in the fluoroorotic acid resistant NIH4215 isolates and the frequency of mutation was by at least one order of magnitude higher than that observed for the clinical A. fumigatus isolate CBS144.89. In summary, despite its virulence in animal models, strain NIH4215 is a thiamine auxotroph and prone to accumulate mutations. Our results suggest that thiamine biosynthesis is dispensable for host infection and mutation-prone strains such as NIH4215 could potentially facilitate the evolution of azole resistant strains as increasingly observed in the environment.